The Main Directions and Importance of the Establishment of the Educational Sector with Production Enterprises - Samadova Malika Xasan qizi (Genius Publishing Group, 2022)
In the developing economic environment, the issue of forming a new system of relations between the educational organization and enterprises, employers' associations is becoming more and more urgent. In the plans for the development of secondary vocational education, the issues of studying the labor market and interacting with partners occupy an important place. The main social partners are educational organizations, industrial enterprises, scientific organizations, state administration bodies and public organizations. The article shows the importance, content, forms and main directions of cooperation in production and educational institutions
Keywords: Early motivation; prospective determination; interdependence; synergy